2023
DOI: 10.3390/molecules28020599
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Antioxidant, Clinical Enzyme Inhibitory Properties and Cytotoxic Potential of Tambourissa peltata Baker—An Understudied Endemic Plant

Abstract: This study documents for the first time the phytochemical composition and biological activities of Tambourissa peltata Baker, an endemic plant from Mauritius. Phytochemical extraction was performed using ethyl acetate, methanol and distilled water as solvents. The phytochemical composition was determined through HPLC-MS and other standard assays. The DPPH, ABTS, FRAP, CUPRAC and phosphomolybdenum assays were employed for the determination of the antioxidant potential, whereas cell viability assays were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Likewise, Raj et al [8] described the tyrosinase enzyme inhibitory activity of essential oil of different guava cultivars, and the highest inhibition was recorded with an IC 50 of 133.45 µg/mL for the Karela cultivar and it was relatively lesser than the results observed in the present report. Suroowan et al [41] analyzed the tyrosinase enzyme inhibitory effect of the Tambourissa peltata leaf and revealed that the methanolic extract (155.30 ± 0.55 mg KAE/g) had a better inhibition effect among ethyl acetate and distilled water extracts and this also supports the results of the present study that recorded the highest percentage of inhibitions in methanolic extracts.…”
Section: Free Radical Scavenging Potential Of Guava Cultivarssupporting
confidence: 88%
“…Likewise, Raj et al [8] described the tyrosinase enzyme inhibitory activity of essential oil of different guava cultivars, and the highest inhibition was recorded with an IC 50 of 133.45 µg/mL for the Karela cultivar and it was relatively lesser than the results observed in the present report. Suroowan et al [41] analyzed the tyrosinase enzyme inhibitory effect of the Tambourissa peltata leaf and revealed that the methanolic extract (155.30 ± 0.55 mg KAE/g) had a better inhibition effect among ethyl acetate and distilled water extracts and this also supports the results of the present study that recorded the highest percentage of inhibitions in methanolic extracts.…”
Section: Free Radical Scavenging Potential Of Guava Cultivarssupporting
confidence: 88%
“…Orchidaceae tubers [194] Anacardium occidentale Anacardiaceae leaves [195] Anacardium occidentale Anacardiaceae fruits [196] Andropogon virginicus Poaceae aerial parts [197] Angelica keiskei Umbelliferae leaves, roots [198] Arachis hypogaea Fabaceae peanut shell [154] Areca catechu Palmaceae fruits [195] Arctium minus Asteraceae flower heads, leaves, roots [199] Artemisia verlotiorum Asteraceae whole plant [200] Atractylodis macrocephalae Asteraceae rhizomes [201] Berberis thunbergii Berberidaceae leaves [202] Bergenia pacumbis Saxifragaceae plant and its rhizomes [203] Blepharis linariifolia Acanthaceae aerial parts [204] Bletilla striata Orchidaceae tubers, fibrous roots [205] Breynia retusa Phyllanthaceae leaves [206] Bridelia ferruginea Phyllanthaceae leaves, stem bark [207] Bruguiera gymnorhiza Rhizophoraceae leaves, roots, fruits [158] Cakile maritima Brassicaceae fruits, leaves, stems [208] Cannabis sativa Cannabaceae seeds [169] Carthamus tinctorius Asteraceae seeds [209] Celastrus hindsii Celastracea leaves [210] Cercis glabra Fabaceae leaves [211] Cladium mariscus Cyperaceae seeds [212] Clausena indica Rutaceae roots [213] Combretum micranthum Combretaceae leaves [196] Crotalaria burhia Fabaceae aerial parts, roots [214] Croton hirtus Euphorbiaceae aerial parts [215] Cudrania tricuspidata Moraceae fruits [216] Cytinus hypocistis Cytinaceae aerial parts [217] Dianella ensifolia Liliaceae roots [218] Dodonaea viscosa Sapindaceae stems [219] Elaeagnus angustifolia Elaeagnaceae fruits, leaves [220] Table 4. Cont.…”
Section: Anacamptis Pyramidalismentioning
confidence: 99%
“…Schisandraceae fruits [249] Secamone afzelii Asclepiadaceae leaves [250] Streblus taxoides Moraceae wood [251] Strobilanthes glutinosus Acanthaceae whole plant [252] Tambourissa peltat Monimiaceae fruits, flowers, leaves [200] Vitis amurensis Vitaceae root [253] Vitis vinifera Vitaceae seeds [169] Warburgia salutaris Canellacea barks [167] Zingiber kerrii Zingiberaceae rhizomes [254] Ziziphora taurica Lamiaceae aerial parts [255] The in vitro spectrophotometric enzyme tyrosinase inhibition assay was used to measure anti-tyrosinase activity, compared with kojic acid or β-arbutin as a reference tyrosinase inhibitor.…”
Section: Schisandra Chinensismentioning
confidence: 99%
“…In the search for promising drug candidates, some investigators have allowed their research work to be guided by the medicinal uses of endemic plants, intending to elucidate the active ingredients and validate their purported therapeutic claims [37,39,[46][47][48][49][50]54,55,61,67,68]. Meanwhile other scientists have randomly screened the unexplored unique floral reserve, aiming to evaluate the health benefits of these endangered plant species before their permanent loss due to extinction [32][33][34]51,63]. Yet, a pre-clinical drug candidate budding from the endemic resources of Mauritius is beyond the horizon.…”
Section: Key Challenges and Future Workmentioning
confidence: 99%